Influence of nonlinear dissipation and external perturbations on transition scenarios to the chaos in the Lorenz-Haken system - Dvornichenko, A.V. (Functional Materials, 2013)
We studied an influence of nonlinear dissipation and external perturbations on transition scenarios to the chaos in the Lorenz-Haken system. It was shown that variation in the values of external potential parameters leads to parameters domain formation which results in the chaos appearance. We have found that in the modified Lorenz-Haken system transitions from the regular to chaotic dynamics can be of Ruelle-Takens scenario, Feigenbaum scenario, or through intermittency.